2014
DOI: 10.1371/journal.pone.0104971
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Intralipid®- but Not Sevoflurane-Mediated Cardioprotection in Early Type-2 Diabetic Hearts of Fructose-Fed Rats: Importance of ROS Signaling

Abstract: BackgroundInsulin resistance and early type-2 diabetes are highly prevalent. However, it is unknown whether Intralipid® and sevoflurane protect the early diabetic heart against ischemia-reperfusion injury.MethodsEarly type-2 diabetic hearts from Sprague-Dawley rats fed for 6 weeks with fructose were exposed to 15 min of ischemia and 30 min of reperfusion. Intralipid® (1%) was administered at the onset of reperfusion. Peri-ischemic sevoflurane (2 vol.-%) served as alternative protection strategy. Recovery of le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…Of relevance to the issue raised by Kolwicz et al (1), we have also reported the effects of Intralipid postconditioning in type 2 diabetic rat hearts (4). Our experiments showed that Intralipid completely lost its protective action in diabetic hearts.…”
supporting
confidence: 72%
“…Of relevance to the issue raised by Kolwicz et al (1), we have also reported the effects of Intralipid postconditioning in type 2 diabetic rat hearts (4). Our experiments showed that Intralipid completely lost its protective action in diabetic hearts.…”
supporting
confidence: 72%
“…Carnitine palmitoyltransferase (CPT) activity was measured in mitochondrial samples using 5,5′‐dithiobis‐(2‐nitrobenzoic acid) (DTNB) to monitor the release of reduced CoA liberated from palmitoyl‐CoA by CPT at 412 nm, as previously described (Lou et al. 2014). β ‐hydroxyacyl‐CoA dehydrogenase ( β ‐HCAD) activity of mitochondrial isolates was measured in buffer containing 97 mmol L −1 potassium phosphate, and 100  μ mol L −1 NADH, pH 7.3.…”
Section: Methodsmentioning
confidence: 99%
“…Aconitase activity was assayed as previously outlined (Lou et al. 2014). Oxalomalate (2 mmol L −1 , Cayman), a competitive inhibitor of aconitase, was included in a separate set of samples to ensure assay specificity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their comment, Zaugg et al (1) highlighted some of their recent work investigating the effects of Intralipid administration on postischemic outcomes in rat models of both healthy nondiabetic (2) and early diabetic hearts (3). This was prodded by a discussion point raised in a recent article by my colleagues and I on whether the provision of a mixture of unsaturated fats, such as Intralipid, could improve functional recovery in the ischemic, diabetic myocardium (4).…”
mentioning
confidence: 99%